1998
DOI: 10.1038/sj.bmt.1701533
|View full text |Cite
|
Sign up to set email alerts
|

Poor outcome of autologous stem cell transplantation for adult T cell leukemia/lymphoma: a case report and review of the literature

Abstract: Summary:A limited number of patients with adult T cell leukemia/lymphoma (ATL) who received autologous stem cell transplantation (ASCT) have been reported. We report here a case of fatal systemic Candida krusei infection in a female patient with ATL undergoing ASCT. All of the eight patients (including seven patients in the literature) with ATL who received ASCT developed relapse of ATL or death due to ASCT complication, irrespective of subtype or remission state of ATL, source or selection of SCT or condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
73
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(74 citation statements)
references
References 8 publications
0
73
0
1
Order By: Relevance
“…Tsukasaki et al 22 reported a single case and found seven other reported cases in the literature. The outcome was grim with disease progression noticed within 10 months in all but one patient who had a remission lasting for 26 months.…”
Section: Outcome Of Transplantationmentioning
confidence: 96%
See 1 more Smart Citation
“…Tsukasaki et al 22 reported a single case and found seven other reported cases in the literature. The outcome was grim with disease progression noticed within 10 months in all but one patient who had a remission lasting for 26 months.…”
Section: Outcome Of Transplantationmentioning
confidence: 96%
“…Autologous transplantation was rarely attempted and did not yield success. 22 Allogeneic transplantation was first reported in 1987 by Sobue et al 23 After myeloablative conditioning, the recipient received BM graft from a matched sibling and went on to achieve CR only to die on day 205 due to interstitial pneumonitis. It was not until 1996 that Borg et al 5 reported the first successful allogeneic transplant.…”
Section: Transplantation Therapeutic Optionsmentioning
confidence: 99%
“…1,7 Although high-dose therapy and autologous stem cell transplantation have been shown to improve prognoses in other poor-risk aggressive lymphomas, outcomes for ATL remain poor due to high relapse rates and complications. 2 Utsunomiya et al 5 recently reported promising results for allo-SCT in patients with ATL. However, HLAmatched siblings are seldom available to these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Intensified chemotherapy and/or autologous stem cell transplantation have not yet improved this prognosis. 1,2 Although some successful cases of allogeneic stem cell transplantation (allo-SCT) have been reported, [3][4][5] HLA-matched and HTLV-1 seronegative siblings are available to only a small number of patients.…”
mentioning
confidence: 99%
“…Autologous stem cell transplantation (SCT) is generally ineffective for leukemic or lymphomatous ATLL [45]. The role of allogenic SCT for ATLL remains unclear [46][47][48][49][50][51][52].…”
Section: Stem Cell Transplantationmentioning
confidence: 99%